Examining the developments in scheduling algorithms research: A bibliometric approach - Temidayo Oluwatosin Omotehinwa (Heliyon, 2022)
This study examined the developments in the field of Scheduling algorithms in the last 30 years (1992–2021) to help researchers gain new insight and uncover the emerging areas of growth for further research in this field. This study, therefore, carried out a bibliometric analysis of 12,644 peer-reviewed documents extracted from the Scopus database using the Bibliometrix R package for bibliometric analysis via the Biblioshiny web interface. The results of this study established the development status of the field of Scheduling Algorithms, the growth rate, and emerging thematic areas for further research, institutions, and country collaborations. It also identified the most impactful and leading authors, keywords, sources, and publications in this field. These findings can help both budding and established researchers to find new research focus and collaboration opportunities and make informed decisions as they research the field of scheduling algorithms and their applications.